Sanskrit Event Verbs in the Bhagavad Gita: A Natural Semantic Metalanguage Analysis - Ni Nyoman Tri Gitayani; Ni Luh Sutjiati Beratha; I Made Rajeg (International Journal of Multilingual Education and Applied Linguistics, 2026)
Sanskrit verbs constitute a compelling object within linguistic research because of their semantic and structural complexity, which has not yet been widely explored. A proper understanding of Sanskrit verb usage can help prevent errors, especially among Hindus who use the language in cultural or religious contexts. Therefore, this research aims at analyzing the structure and semantic role of Sanskrit event verbs through the Natural Semantic Metalanguage approach. The data sources were from three chapters of the Bhagavad Gita (Chapters IX, X, and XI). The data were gathered using documentation and systematic note-taking techniques, and subsequently analyzed through qualitative methods by implementing the Natural Semantic Metalanguage approach conducted by Wierzbicka, supported by the semantic macroroles theory by van Valin and Lapolla. From this research, five Sanskrit event verbs were found in those chapters, namely cyavanti “to fall down”, pravartate “to develop”, vepamānaḥ “to tremble”, abhivijvalanti “to blaze”, and pratapanti “burns”. Further analysis showed that these event verbs can be classified into MOVE and HAPPEN types. In addition, the semantic macroroles of the Sanskrit event verb arguments found can be identified in the form of AGENT, PATIENT, EXPERIENCER, SOURCE, and THEME.